2020
DOI: 10.1021/acs.energyfuels.0c01886
|View full text |Cite
|
Sign up to set email alerts
|

Methane Absolute Adsorption in Kerogen Nanoporous Media with Realistic Continuous Pore Size Distributions

Abstract: Accurate estimation of CH 4 absolute adsorption amount is essential for shale gas-in-place (GIP) evaluation as well as well productivity. Recent studies have shown that pore size distribution (PSD) plays an important role in determination of the absolute adsorption. However, previous studies only contain some discretized pore sizes, while a continuous PSD has not been fully taken into account. In this work, CH 4 adsorption behaviors in various nanopores are first investigated via the grand canonical Monte Carl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 80 publications
(166 reference statements)
0
13
0
Order By: Relevance
“…99,279 In this regard, the OK lattice model can capture varying methane adsorption behaviors in micropores and mesopores, and by coupling with PSD, it can have a good agreement with molecular simulations in terms of methane absolute adsorption in model kerogen nanoporous media. 100 However, rock heterogeneity has not been fully taken into account in the present study nor has it been treated without correlating with actual rock composition analysis. Furthermore, the effect of pore geometry has not been investigated well, while most conversion methods are based on slit geometry.…”
Section: Summary About Various Conversion Methods Andmentioning
confidence: 99%
See 4 more Smart Citations
“…99,279 In this regard, the OK lattice model can capture varying methane adsorption behaviors in micropores and mesopores, and by coupling with PSD, it can have a good agreement with molecular simulations in terms of methane absolute adsorption in model kerogen nanoporous media. 100 However, rock heterogeneity has not been fully taken into account in the present study nor has it been treated without correlating with actual rock composition analysis. Furthermore, the effect of pore geometry has not been investigated well, while most conversion methods are based on slit geometry.…”
Section: Summary About Various Conversion Methods Andmentioning
confidence: 99%
“…It is shown that the gas adsorption capacity in organic matter is generally larger than that in inorganic matter. 29,70,307 In addition, molecular simulations show that the methane maximum excess adsorptions in carbon micropores and mesopores at 333.15 K are within the range of 0.0036−0.006 mmol/m 2 , 100 while those in illite are within the range of 0.0017−0.0024 mmol/m 2 . 99 Similar observations have been reported as listed in Table 5.…”
Section: Molecular Simulations On Methane Adsorptionmentioning
confidence: 95%
See 3 more Smart Citations